Safety and immunogenicity of a soluble native Neospora caninum tachyzoite-extract vaccine formulated with a soy lecithin/β-glucan adjuvant in pregnant cattle - Mansilla, Florencia Celeste (2015)
The global economic impact of Neospora caninum infection in cattle herds has promoted the development of vaccines that can be safely used during pregnancy. The aim of this study was to evaluate the safety and immunogenicity of a vaccine formulated with the soluble fraction of tachyzoite's lysate and a soy-based aqueous adjuvant (sNcAg/AVEC), which was protective in the mouse model and induced strong IFN-γ responses and high avidity antibodies in non-pregnant cattle. Ten pregnant heifers were vaccinated twice during the first trimester of gestation and 8 remained unvaccinated. Anti- N. caninum immune responses were efficiently primed by vaccination, evidenced by a quick induction of IgM serum titers (7. dpv) and a prompt switch to high avidity IgG shortly after infection (performed at 78 or 225 days of gestation; n= 5 each); while naïve cattle elicited lower IgG titers, with a delayed kinetics. High systemic IFN-γ levels were induced after infection which did not interfere with pregnancy. No local or systemic adverse effects were recorded along the study. Calves were born in term and in good health conditions, showing that the sNcAg/AVEC vaccine was safe when applied to healthy heifers during the first trimester of gestation.